PENERAPAN STRATEGI VALUE PRICING PADA PERUSAHAAN - Tedjo, Esther (Fakultas Ekonomi Universitas Wisnuwardhana, 2015)
Choosing a pricing objective and associated strategy is animportant function or the business owner and integral part of thebusiness plan. The important of strategy of pricing is how the companyreach their goal or profit what their want. The fact that all customerswant good products and no customers want to overpay. Regardless ofthe product category, it is the customers’ perception of value that willdetermine which vendor gets their business. For this reason, it isimportant for companies who make and price products to understandhow much their products are worth.Kata Kunci : Value pricing, Strategic, Price, EDLP, HLP